PENERAPAN MODEL PEMBELAJARAN OTAK ATIK OTAK (OAO) DALAM PEMBELAJARAN PERKALIAN BILANGAN BULAT MELALUI PENDAMPINGAN - Priyono; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Improving teacher performance related to the learning process through this assistance aims to improve the ability of teachers to carry out the learning process using the Otak Atik Otak (OAO) learning model at teachers at SD Negeri Ngemplak, Kalibawang, Kulon Progo district. The steps used by researchers through this assistance use a type of school action research (PTS) which is carried out for 2 cycles. Where each cycle consists of 2 meetings. The improvement steps are based on research methods/procedures, which are carried out based on the stages of planning, implementation, observation, and reflection. The subject of the study was a teacher at SD Negeri Ngemplak, Kalibawang, Kulon Progo Regency, totaling 5 people. The object of study is the application of the Brain Atik Brain (OAO) learning model in mathematical learning of multiplication material. The results of preliminary observations of the quality of learning practices carried out by teachers still have many shortcomings seen in the table above the average score is: 2.36; the percentage reached 47.14%; category "Not good" so that a research action was carried out whose results of cycle I meeting 1 were proven on the acquisition of average scores achieved; 2,84; percentage 58.80%; category "Unsatisfactory", subsequently cycle I meeting 2 quite satisfactory results, evident in the acquisition of the average score achieved; 4,21; percentage 84.27%; category "Quite Satisfying". Cycle II of meeting 1 observation results obtained data on the ability of teachers to use the OAO model; after observation, an average score was obtained; 4,47; percentage reached; 89,33; while cycle II of meeting 2, the ability of teachers to use the OAO model in mathematics learning as a result of observation average score reached 4.81; the percentage reached 96.27%; Thus the Brain Atik Otak (OAO) model has a significant impact on teachers in carrying out the mathematical learning process.